Artificial Intelligence as a Service, Economic Growth, and Well-Being. (November 2022) - Makridis, Christos A.; Mishra, Saurabh
The share of artificial intelligence (AI) jobs in total job postings has increased from 0.20% to nearly 1% between 2010 and 2019, but there is significant heterogeneity across cities in the United States (US). Using new data on AI job postings across 343 US cities, combined with data on subjective well-being and economic activity, we uncover the central role that service-based cities play to translate the benefits of AI job growth to subjective well-being. We find that cities with higher growth in AI job postings witnessed higher economic growth. The relationship between AI job growth and economic growth is driven by cities that had a higher concentration of modern (or professional) services. AI job growth also leads to an increase in the state of well-being. The transmission channel of AI job growth to increased subjective well-being is explained by the positive relationship between AI jobs and economic growth. These results are consistent with models of structural transformation where technological change leads to improvements in well-being through improvements in economic activity. Our results suggest that AI-driven economic growth, while still in the early days, could also raise overall well-being and social welfare, especially when the pre-existing industrial structure had a higher concentration of modern (or professional) services.